Delivering interlaminar reinforcement in composites through electrospun nanofibres - T. R. Pozegic (Taylor & Francis Group, 2019)
Electrospun nonwoven veils comprising thermoplastic fibres (average diameter 400–600 nm) based on polysulfone (PSU), polyamide (PA-6,6), and polyetherimide (PEI) have been fabricated and used as interlaminar reinforcements in carbon fibre composites containing a commercial epoxy resin (8552/IM7). Samples were tested for their interlaminar properties and improvements were observed in the initial mode I interlaminar toughness of 30% (PA-6,6), 36% (PEI), and 44% (PSU), while improvements of 7% (PSU) and 8% (PEI) were observed in the propagation of the mode I interlaminar toughness. A reduction of 11% was observed for the propagation of the mode I interlaminar toughness for PA-6,6. Post-testing analysis of the cross-section and the fracture surface revealed that the crack front avoids the reinforcement significantly for PA-6,6. For mode II, however, this failure mechanism leads to improvements of 30% in interlaminar toughness for the PA-6,6, whereas the other reinforcements display negligible (PEI) and 31% reduction (PSU) interlaminar toughness.